Aggregation induced emission: Concluding Remarks. (31st January 2017) - Liu, Bin; Zhang, Ruoyu
Abstract : This article presents the Closing Remarks of the Faraday Discussion on aggregation induced emission (AIE) held in Guangzhou, China in November 2016. The history of the AIE phenomenon is summarized, from its discovery and mechanistic studies to real-life applications in optoelectronics, environmental monitoring and biomedical research. The paper concludes with comments on the future perspectives of the field.